One-part sodium carbonate-activated slag/r-MgO based mixes: Influence of nano-silica incorporation on compressive strength and microstructural development - Ozen, Omer Can; Oktay, Didem; Akturk, Busra (ELSEVIER SCI LTD, 2024)
In this study, environment -friendly one -part alkali -activated slag -based mixes were prepared by using solid sodium carbonate as the alkali activator and incorporating reactive MgO (r-MgO) as the additive. Substitution of rMgO in reference mixes was carried out at various levels, up to 15%, to enhance the reaction mechanism and strength development. The strength development was measured up to 56 days and analyzed microstructurally using Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric, and scanning electron microscopy analyses. Additionally, the influence of incorporating nano -silica in the binary mixes on strength development and microstructure was investigated. It was observed that the reaction mechanism could be improved by incorporating a low amount of reactive MgO, leading to expedited setting time and significant increases at both early age and final compressive strength values. Nano -silica incorporation was found to be effective in improving compressive strength at all ages, resulting in the formation of a higher matrix phase as demonstrated by microstructure tests. The highest compressive strength was attained in the nano -silica and rMgO incorporating ternary mixes, reaching 25.9 MPa on the 3rd day and 47.2 MPa on the 28th day after production. Furthermore, the environmental impacts of the produced mixes were assessed. This study highlights the feasibility of one -part sodium carbonate -activated slag -based materials, especially with r-MgO inclusion, and underscores the role of nano -silica incorporation in enhancing strength properties.
Keywords: Sodium carbonate; One -part mixing; Nano -silica; Compressive strength; Microstructure; BLAST-FURNACE SLAG; C-S-H; FLY-ASH; REACTIVE MGO; MECHANICAL-PROPERTIES; HYDRATION PROPERTIES; THERMAL-PROPERTIES; REACTION-KINETICS; DRYING SHRINKAGE; CEMENT PASTE; Construction & Building Technology; Engineering; Materials Science